Quality of life in infertile patients in Brazil: religious spirituality as a coping mechanism - Oppenheimer, Drauzio; Peres Caldas, Christiane; Menin da Fonseca, Giovanna Cazelato; Fernandes, Cecília Rezende; Rego, Francisca; Nunes, Rui (Acta Bioethica, 2025)
Due to social pressure and individual desire to have children, infertility is often accompanied by suffering and decreased quality of life. Among possible coping mechanisms, religion has been suggested to help improve quality of life. The objective of this study was to verify, in a cohort of Brazilian women undergoing infertility treatment, if there is a relationship between religiosity and quality of life. The sample consisted of 104 volunteer Brazilian women who sought infertility treatment. A FertiQoL and a Religiosity questionnaire were administered. Descriptive statistics were computed, and groups were compared using a Chi-square test. Most of the participants in the study stated that religiosity was associated with well-being, and 90% of them concluded that religiosity was an important process during infertility treatment. The study found that religiosity leads to improved adaptive coping capacity. Although it is difficult to demonstrate causality, results strongly suggest that religiosity plays an important role in adjusting the psychological aspects of infertile women.